2016
DOI: 10.1245/s10434-016-5127-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of Extended Thromboprophylaxis After Abdominal and Pelvic Surgery in Cancer Patients: A Systematic Review and Meta-Analysis

Abstract: ETP after abdominal or pelvic surgery for cancer significantly decreased the incidence of all VTEs and proximal DVTs, but had no impact on symptomatic PE, major bleeding, or 3-month mortality. ETP should be routinely considered in the setting of abdominal and pelvic surgery for cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(91 citation statements)
references
References 27 publications
4
87
0
Order By: Relevance
“…44 27 Based upon these data, the current NCCN and ASCO guidelines recommend extended-duration prophylaxis for high-risk abdominal-pelvic cancer surgery patients. 23,24 In a prospective multicenter observational study of ambulatory cancer patients receiving chemotherapy, Khorana et al noted that 1.9% of patients developed VTE during a median follow up of 2.4 months.…”
Section: What Is the Risk Of Venous Thromboembolism (Vte) In Cancer Pmentioning
confidence: 99%
“…44 27 Based upon these data, the current NCCN and ASCO guidelines recommend extended-duration prophylaxis for high-risk abdominal-pelvic cancer surgery patients. 23,24 In a prospective multicenter observational study of ambulatory cancer patients receiving chemotherapy, Khorana et al noted that 1.9% of patients developed VTE during a median follow up of 2.4 months.…”
Section: What Is the Risk Of Venous Thromboembolism (Vte) In Cancer Pmentioning
confidence: 99%
“…Prolonged thromboprophylaxis with LMWH was also (42)(43)(44). It can therefore be inferred that extended prophylaxis is beneficial for surgical patients with high risk for VTE and especially those suffering from malignancy.…”
Section: Duration Of Prophylaxismentioning
confidence: 99%
“…A recent meta‐analysis included 39 studies comparing perioperative pharmacological thromboprophylaxis in cancer patients undergoing surgery with no pharmacological prophylaxis (including mechanical prophylaxis or no prophylaxis), and demonstrated 50% reduction in the rate of deep vein thrombosis (DVT) with pharmacological prophylaxis, with an acceptable increase in the risk of bleeding, without a difference in mortality and pulmonary embolism (PE) 23. In addition, a systemic review and meta‐analysis on seven randomized studies (encompassing 4807 patients) showed that extended thromboprophylaxis (2‐6 weeks) after an abdominopelvic cancer surgery significantly reduced the risk of all VTE and proximal DVT by approximately 50%, when compared with conventional duration of thromboprophylaxis (<2 weeks) 24. No difference was found in the incidence of symptomatic PE, major bleeding events, and 3‐month all‐cause mortality 24.…”
Section: Primary Prevention Of Thrombosis In Cancer Patientsmentioning
confidence: 99%
“…In addition, a systemic review and meta‐analysis on seven randomized studies (encompassing 4807 patients) showed that extended thromboprophylaxis (2‐6 weeks) after an abdominopelvic cancer surgery significantly reduced the risk of all VTE and proximal DVT by approximately 50%, when compared with conventional duration of thromboprophylaxis (<2 weeks) 24. No difference was found in the incidence of symptomatic PE, major bleeding events, and 3‐month all‐cause mortality 24. Given this evidence, pharmacological thromboprophylaxis is recommended for most cancer patients undergoing surgery, with extended prophylaxis (4 weeks) for patients undergoing abdominopelvic cancer surgery 25, 26…”
Section: Primary Prevention Of Thrombosis In Cancer Patientsmentioning
confidence: 99%